Hacia una imagen contextualista de la racionalidad - Xiang, Huang (2008)
Empirical studies of experimental psychology have shown that it is questionable the traditional concept of rationality, according to which, to be rational is to reason in accordance with principles of reasoning that are based on rules of logic, probability theory, and so forth. An alternative way to understand rationality suggested by many psychologists and philosophers insists that the normative principles of reasoning should be understood within the context under which their application is correct. This paper aims to examine the plausibility of this contextualist image of rationality. After characterizing the traditional concept of rationality in the first section, in the second section I study the arguments from psychological experiments of reasoning against the traditional concept. In the third section, the contextualist image of rationality is presented and I argue why this image is plausible.